Examining the Impact of Teaching Strategies and Reading Habits on Students’ Reading Comprehension - Husni Mubarok; Nina Sofiana (Fakultas Bahasa dan Budaya Asing (FBBA), Universitas Muhammadiyah Semarang, 2018)
This study investigated the impact of two teaching strategies of cooperative learning; Teams Games Tournaments (TGT) and Student Team Achievement Divisions (STAD) on reading comprehension achievement of Junior High School students with different reading habits. After 34 students in experimental and control class did a pre-test, they were treated by using TGT and STAD. The students were also assigned into two group reading habits; high and low. The experimental group received treatment of TGT whereas the control group was treated by STAD. Then, a post-test was administered, and its results were analyzed through two-way ANOVA. The results revealed that TGT and STAD are effective in improving students’ reading comprehension where F ratio (28.846) ˃ F table (3.99), but on the other side, students’ reading habit, both high and low, cannot affect students' reading comprehension. It was also concluded that there was no interaction effect between teaching strategies and reading habits on students’ reading comprehension.Keywords: teaching strategies, TGT, STAD, reading habit.